Dampak Alat Pembayaran QRIS terhadap Omzet Penjualan Pedagang Kuliner - Indriyani Dwi Putri; Keisha Azahra Fauzita; Agnevia Nursianda; Firda Aulianti; Elva Hanov Rais; Nelly Kristin Sibarani; Rama Wijaya Abdul Rozak (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The purpose of this research is to describe the impact of using QRIS digital payment tools on the turnover of culinary traders. The research method used is descriptive qualitative by conducting direct interviews as a data collection instrument. Involving 20 culinary merchants in the Gegerkalong area, Bandung, West Java, this study aims to comprehensively understand the impact of using QRIS in the daily operational activities of merchants, as well as to explain the potential changes in sales turnover that may occur after QRIS adoption. The results show that the use of QRIS provides benefits in simplifying transactions, improving business efficiency, and facilitating cashless payments. Although there are some barriers such as technical issues, administrative costs, and lack of public understanding, the use of QRIS has the potential to increase the income of culinary merchants, especially in facilitating transactions with customers who prefer non-cash methods. In conclusion, the adoption of QRIS in culinary businesses can provide significant benefits in expanding the reach of digital payments and improving operational efficiency.